Flood Mitigation in Malang City: The Perspective of Health Policy - Mohammad Muhibbin; Umar Sahid Sugiharto; Budi Parmono (Journal of Global Pharma Technology, 2020)
Objective: The high intensity of rainfall in Indonesia causes some cities to experience flood, including Malang City. Malang is a mountainous city which is located on highlands, between 444 to 667 meters above sea level. Ironically, every year during the rainy season, many parts of Malang are hit by flood. This flood disaster causes severe health problems. This paper aims to describe the flood mitigation in Malang City. Method: The method used in this research is the socio-legal research. It uses the cultural socio-legal approach, with the background of the thought that the law cannot be separated from the lives of the people, in the form of values, attitudes, behaviors, and impacts which it causes. Results: The results of this research show that the main cause of the flood is influenced by human activities as the main factor. Conclusion: The government should make policies in preventing the health impacts caused by flood.